1996
DOI: 10.1104/pp.112.3.1245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Temperature on Photosynthesis in Beans (I. Oxygen Evolution and Chlorophyll Fluorescence)

Abstract: We studied the effect of increasing temperature on photosynthesis i n two bean (Phaseolus vulgaris L.) varieties known to differ in their resistance to extreme high temperatures, Blue Lake (BL), commercially available i n the United Kingdom, and Barbucho (BA), noncommercially bred in Chile. We paid particular attention to the energy-transducing mechanisms and structural responses inferred from fluorescence kinetics. The study was conducted in nonphotorespiratory conditions. lncreases in temperature resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
78
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(87 citation statements)
references
References 25 publications
9
78
0
Order By: Relevance
“…High temperatures, on the other hand, provoke heat stress and accelerate the respiration (Abele et al 2002) and the photosynthetic rates (Pastenes and Horton 1996), leading to overproduction of reactive oxygen species that affect plant growth and productivity.…”
Section: Mapks and Temperature Stressesmentioning
confidence: 99%
“…High temperatures, on the other hand, provoke heat stress and accelerate the respiration (Abele et al 2002) and the photosynthetic rates (Pastenes and Horton 1996), leading to overproduction of reactive oxygen species that affect plant growth and productivity.…”
Section: Mapks and Temperature Stressesmentioning
confidence: 99%
“…First, elevated leaf temperatures that accompany high irradiance have been shown to cause metabolic imbalances (Pastenes and Horton, 1996b), deleterious effects on thylakoid function (Pastenes and Horton, 1996a), enhanced photoinhibition (Fuse et al, 1993), and enhanced photorespiration (Leegood and Edwards, 1996).…”
mentioning
confidence: 99%
“…The oldest and most widely accepted idea is that isoprene stabilizes chloroplast membranes (Sharkey and Singsaas, 1995). Thylakoid membranes become leaky at high temperature (Pastenes and Horton, 1996;Bukhov et al, 1999;Schrader et al, 2004;. It was suggested that the positive effect of isoprene might be due to the hydrophobic nature of the molecule, the localization of isoprene synthase enzyme near the thylakoid membranes (Wildermuth and Fall, 1998;Schnitzler et al, 2005), and the high octanol/water partitioning coefficient (Copolovici and Niinemets, 2005).…”
mentioning
confidence: 99%